Exploratory data analysis and success prediction of Google Play Store apps - Mueez, Abdul; Ahmed, Khushba; Islam, Tuba; Iqbal, Waqqas (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.